Efektifitas Konseling Behavioral Dengan Menggunakan Teknik Modeling Untuk Mengurangi Perilaku Kecanduan Game Online (Studi Pada Peserta Didik Kelas XI IPS 2 SMA NegerI 1 Batang Anai Kabupaten Padang Pariaman) - Iga Ngesti; Fitria Kasih; Joni Adison (Journal on Education, 2023)
The background of this research is that in this school there are still students who have online game addiction behavior. The purpose of this research is to describe; 1). Prior to being given behavioral counseling services using modeling techniques. 2). After that, behavioral counseling services were given using modeling techniques. 3). The effectiveness of behavioral counseling using modeling techniques to overcome online game addiction in students. The research was conducted using a descriptive quantitative experimental method. The population of this research is 6 students. The sample was selected using a purposive sampling technique, namely 2 students. The instrument used is a questionnaire. As for data analysis using the Paired Sample T test. Based on the results of research on: The effectiveness of behavioral counseling using modeling techniques to reduce online game addiction. 1). Previously given behavioral counseling services using modeling techniques were in the high and medium categories. 2). after being given behavioral counseling services using modeling techniques are in the very low and low categories. 3). The effectiveness of behavioral counseling services using modeling techniques to reduce online game addiction behavior in students is effective because there is a significant change between pretest and posttest. This research is recommended for counseling teachers who are expected to be able to provide language counseling services by using modeling techniques and utilizing existing facilities and infrastructure in schools.